Course of intellectual functioning in schizophrenia and bipolar disorder: a 10-year follow-up study. Issue 6 (8th April 2023) - Flaaten, Camilla Bärthel; Melle, Ingrid; Gardsjord, Erlend; Bjella, Thomas; Engen, Magnus Johan; Vaskinn, Anja; Åsbø, Gina; Wold, Kristin Fjelnseth; Widing, Line; Lyngstad, Siv Hege; Haatveit, Beathe; Simonsen, Carmen; et al.
Abstract: Background: Intellectual functioning (IQ) is lower in schizophrenia patients compared to healthy controls, with bipolar patients intermediate between the two. Declines in IQ mark the onset of schizophrenia, while stability is generally found post-onset. There are to date few studies on long-term IQ development in bipolar disorder. This study presents 10-year follow-up data on IQ, including premorbid IQ estimates, to track the developmental course from pre-onset levels to long-term outcomes in both patient groups compared to healthy controls. Methods: We included 139 participants with schizophrenia, 76 with bipolar disorder and 125 healthy controls. Mixed model analyses were used to estimate developmental slopes for IQ scores from estimated premorbid level (NART IQ) through baseline (WASI IQ) measured within 12 months post-onset, to 10-year follow-up (WASI IQ), with pairwise group comparisons. The best fit was found using a model with a breakpoint at baseline assessment. Results: Only the schizophrenia group had significant declines from estimated premorbid to baseline IQ levels compared to controls. When comparing patient groups, schizophrenia patients had steeper declines than the bipolar group. Increases in IQ were found in all groups over the follow-up period. Conclusions: Trajectories of IQ from premorbid level to 10-year follow-up indicated declines from estimated premorbid level to illness onset in both patient groups, followed by increases during the follow-up period. Schizophrenia patients had a steeper decline than bipolar patients. During follow-up, increases indicate developmental improvement for both patient groups, but with a maintained lag compared to healthy controls due to lower premorbid levels.